2017
DOI: 10.1038/s41598-017-13643-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Microarchitecture and Biomechanics of the Necrotic Femoral Head

Abstract: The mechanism behind osteonecrosis of the femoral head (ONFH) remains unclear. The aim of this study was to explore the pathogenesis of ONFH from a biomechanical standpoint to provide a theoretical basis for improved treatments. We compared the bone structure of fractured femoral heads with that of necrotic femoral heads by Micro-CT scanning and histological evaluation. In addition, we compared the biomechanical properties of each zone in fractured femoral heads with those in necrotic femoral heads by using bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Regarding the pathogenesis of the femoral head collapse in ONFH, Bullough and DiCarlo proposed that it might result from the focal concentration of stress at the junction between the thin trabeculae of the necrotic zone and the thickened trabeculae of the reparative zone. Similar to previous reports, micro‐CT evaluations in this study showed that in the reparative zone with sclerotic changes, the trabecular thickness was significantly increased compared to that in the necrotic zone. In addition, collapse has been found to consistently involve subchondral fractures at the lateral boundary .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the pathogenesis of the femoral head collapse in ONFH, Bullough and DiCarlo proposed that it might result from the focal concentration of stress at the junction between the thin trabeculae of the necrotic zone and the thickened trabeculae of the reparative zone. Similar to previous reports, micro‐CT evaluations in this study showed that in the reparative zone with sclerotic changes, the trabecular thickness was significantly increased compared to that in the necrotic zone. In addition, collapse has been found to consistently involve subchondral fractures at the lateral boundary .…”
Section: Discussionsupporting
confidence: 91%
“…With conventional clinical computed tomography (CT), detailed analysis of bone-resorptive lesions including their distribution and dimensions has been difficult. However, using micro-CT allows us to evaluate the three-dimensional bone structure of the entire femoral head in detail and quantitatively at the micro-level [6][7][8]. Therefore, the purposes of this study were https://doi.org/10.1016/j.jbspin.2019.09.004 1297-319X/© 2019 Société franç aise de rhumatologie.…”
Section: Introductionmentioning
confidence: 99%
“…ONFH, a common refractory‐related disorder specifically to orthopedics, and it has been two separate categories as traumatic and non‐traumatic. The latter involves more pathogenic factors, and the precise pathogenesis is entirely ambiguous 41 . The utilization of GCs is a substantial cause of non‐traumatic ONFH 42 .…”
Section: Discussionmentioning
confidence: 99%